EFFECT OF DESIZING AND SCOURING ON GEOMETRICAL PROPERTIES OF THECOTTON FABRIC - RITIKA BAMAL, NISHA ARYA, ARPITA GROVER; NEETA (The Journal of Research, PJTSAU, 2026)
Textiles have constantly played a crucial role in the evolution of human culture by being at the forefront of both technological and artistic development. The study investigates the impact of desizing and scouring processes on the geometrical properties of grey cotton fabric, crucial for its functionality in various applications. Through a series of preparatory treatments, including desizing to remove stiffening agents and scouring to eliminate impurities, the fabric’s appearance and physical attributes were enhanced. Geometrical properties such as fabric count, weight, and thickness were examined before and after treatment. The results indicate a notable increase in fabric count, with a 12.38% rise in warp and a 6.4% increase in weft, post-desizing and scouring. Additionally, fabric weight and thickness showed significant increases of 9.5% and 8.6%, respectively, after treatment. These enhancements suggest improved fabric quality, likely attributed to the removal of impurities and the resulting compactness of the weave. Overall, the study underscores the importance of preparatory processes in optimizing cotton fabric properties for diverse textile applications.